2017
DOI: 10.1017/s1930297500005222
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence over the lifespan

Abstract: This research investigated how different forms of overconfidence correlate with age. Contrary to stereotypes that young people are more overconfident, the results provide little evidence that overestimation of one’s performance or overplacement of one’s performance relative to that of others is correlated with age. Instead, the results suggest that precision in judgment (confidence that one knows the truth) increases with age. This result is strongest for probabilistic elicitations, and not present in quantile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Although we suspect that the basic principles (e.g., the inverse U-shaped relationship between mean judgments and variance) will generalize across different populations, more research should be performed to confirm this. Also, because the calibration and bias (e.g., overconfidence) of probability judgments have been shown to vary depending on both culture (Yates, 2010) and age (Prims & Moore, 2017), we can expect these differences to be expressed as differences in sample size and prior distribution (for the Bayesian sampler) or noise probability (for the PTN model). We have no reason to believe that the results depend on other characteristics of the participants, materials, or context.…”
Section: Constraints On Generalitymentioning
confidence: 99%
“…Although we suspect that the basic principles (e.g., the inverse U-shaped relationship between mean judgments and variance) will generalize across different populations, more research should be performed to confirm this. Also, because the calibration and bias (e.g., overconfidence) of probability judgments have been shown to vary depending on both culture (Yates, 2010) and age (Prims & Moore, 2017), we can expect these differences to be expressed as differences in sample size and prior distribution (for the Bayesian sampler) or noise probability (for the PTN model). We have no reason to believe that the results depend on other characteristics of the participants, materials, or context.…”
Section: Constraints On Generalitymentioning
confidence: 99%
“…Possibly, even if individuals solved one or a few training question(s) with high confidence, this success might merely be a coincidence and they do not have enough knowledge to solve further questions. Furthermore, many studies have also demonstrated that people sometimes overestimate their chance of success or actual abilities regarding the domain of the current tasks (i.e., overconfidence [23][24][25][26][27][28][29][30][31]). Based on these considerations, even if the accuracy of group judgments made by individuals with high confidence in one or a few training question(s) is very high, this may decrease for the test questions (see also [32]).…”
Section: Subjective Confidence In "Training" Questions As a Cue For P...mentioning
confidence: 99%
“…Possibly, individuals with extremely high confidence in some question(s) could merely "by chance" solve these question(s) and are in fact, unfamiliar with further questions. In other words, the regression to the mean may occur from training performance to test performance, or individuals with high confidence may make false judgments or overestimate their own abilities, which is known as overconfidence [23][24][25][26][27][28][29][30][31]. Therefore, when a group comprises only individuals with high confidence (called the "highconfidence group"), its training accuracy is unlikely to predict its test accuracy.…”
Section: Mixing Various Confidence Levels In One Group: a Possible St...mentioning
confidence: 99%
“…In other words, having exaggerated or inflated self-efficacy beliefs, i.e. operating under the influence of the Dunning–Kruger effect, may result in overconfidence regarding a specific skill or ability (Canady and Larzo, 2022; Prims and Moore, 2017). People who have a high level of self-efficacy beliefs are less likely to allocate a significant amount of effort to a given task.…”
Section: Literature Reviewmentioning
confidence: 99%